2020
DOI: 10.18203/2320-6012.ijrms20204884
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in health seeking behaviour among tribal pregnant women in a hilly tribal area of Kashmir: a qualitative study

Abstract: Background: Maternal health is of paramount concern all over the world and has been a priority in India as well with the maternal health programs evolving over the time, addressing new arenas and overcoming challenges to reach the Maternal mortality ratio (MMR) target with quality. (1) In tribal areas various barriers in health seeking behavior are impediments towards maternal health.Methods: An explorative qualitative study was undertaken in a tribal area of Srinagar, Kashmir, which is a rural field practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…A total of 30 studies, including 17 quantitative [ 2 , 4 , 5 , 9 , 11 , 18 , 21 , 22 , 24 , 29 , 30 , 36 , 47 – 51 ], 10 qualitative [ 1 , 8 , 23 , 26 , 35 , 52 56 ], and 3 mix-methods studies [ 25 , 57 , 58 ], reported that lack of knowledge and awareness are prominent barrier, resulting in incomplete or non-utilization of obstetric care services (OCS). Dalal et al [2022] explained that due to a lack of awareness, women were unable to understand the processes and systems followed in the health facilities and felt uncomfortable visiting them, which directly influenced their utilization of OCS [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 30 studies, including 17 quantitative [ 2 , 4 , 5 , 9 , 11 , 18 , 21 , 22 , 24 , 29 , 30 , 36 , 47 – 51 ], 10 qualitative [ 1 , 8 , 23 , 26 , 35 , 52 56 ], and 3 mix-methods studies [ 25 , 57 , 58 ], reported that lack of knowledge and awareness are prominent barrier, resulting in incomplete or non-utilization of obstetric care services (OCS). Dalal et al [2022] explained that due to a lack of awareness, women were unable to understand the processes and systems followed in the health facilities and felt uncomfortable visiting them, which directly influenced their utilization of OCS [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Poor communication between health care providers and women availing OCS was another interpersonal barrier that led to poor utilization of OCS [ 5 , 59 , 60 ]. These types of barriers were primarily found in the forest and hill-dwelling communities as they are socially, culturally, and linguistically different from the mainstream population of India [ 34 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was higher level of prompt treatment-seeking behaviour among guardians of the active reproductive ages of 30–49 years compared to the non-reproductive age groups. This could be attributed to constant messages that these guardians (who were mostly women) receive when they go for other health services such as antenatal care, postnatal and family planning [ 32 ]. In addition to programs that seek to promote treatment-seeking behaviours, key malaria control interventions should leverage on the already existing health services that are provided to guardians.…”
Section: Discussionmentioning
confidence: 99%